2006
DOI: 10.1557/proc-976-0976-ee02-01
|View full text |Cite
|
Sign up to set email alerts
|

Grain Boundary Responses to Local and Applied Stress: An In Situ TEM Deformation Study

Abstract: Deformation experiments at temperatures between 300 and 750 K have been performed in situ in the transmission electron microscope to investigate dislocation interactions and reactions with grain boundaries and other obstacles. Dislocations, both partial and perfect, as well as deformation twins have been observed being emitted from grain boundaries and, in some cases, even the same grain boundary. The ejection of dislocations from the grain boundary can result in its partial or total annihilation. In the latte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It is shown that the barriers for glide through a CTB are significantly higher compared to a regular dislocation glide case (Figure 6a) supporting a significant level of strengthening associated with non-deformation twins. The reemission behavior of an incident dislocation from a CTB is reported experimentally [50]; in this study, we provide the associated energy barrier.…”
Section: Glide Plane Transmission Of Dislocation At the Ctbmentioning
confidence: 82%
“…It is shown that the barriers for glide through a CTB are significantly higher compared to a regular dislocation glide case (Figure 6a) supporting a significant level of strengthening associated with non-deformation twins. The reemission behavior of an incident dislocation from a CTB is reported experimentally [50]; in this study, we provide the associated energy barrier.…”
Section: Glide Plane Transmission Of Dislocation At the Ctbmentioning
confidence: 82%
“…Further investigation of modifying either of these two variables, and the associated change in the mechanism would be one interesting future research. Earlier literature have addressed the details of individual reactions both theoretically and experimentally: (a) incorporation (Asaro and Kulkarni, 2008;Jin et al, 2006;Müllner and Solenthaler, 1997), (b) transmission (Kacher et al, 2014;Zhu et al, 2007), (c) multiplication (Miller et al, 2006), (d) transmission and incorporation (Evans, 1974;Jin et al, 2008;Mahajan and Chin, 1973), and (e) blockage by a Lomer lock formation (Karnthaler, 1978;Wang and Huang, 2006). The relative preference for these reactions bears important implications regarding the macroscopic strength and ductility.…”
Section: Role Of Nano-twinsmentioning
confidence: 99%